Characterisation of mmupudu (mimusops zeyheri) leaf rust in Limpopo Province - Monyela, Shadrack (My University, 2021)
Mimusops zeyheri tree groves made up of seventeen trees collected from communities in Southern Africa were used in this study. The trees had high morphological variations in terms of growth rate, fruit (size and taste) and leaf (shapes and sizes) and their identification was made by communal people from where the trees were collected using their morphological characteristics. Generally, this evergreen tree is drought‒tolerant, salt‒tolerant and highly resistant to root-knot (Meloidogyne spp.) nematodes, along with various other pests. This could probably be attributed to high concentration of latex in aboveground organs. Some typical fungal rust symptoms have been observed believed to be the cause of high leaf abscission in certain groves. Currently, there is no report of leaf rust disease on M. zeyheri plants and the mechanism of resistance to other pests is not documented. The objective of this study was to (i) identify the pathogen associated with M. zeyheri leaf rust symptoms using morphological technique and to (ii) determine levels and types of potential defence chemicals and endophytes in M. zeyheri. Samples of M. zeyheri leaves showing rust like symptoms were collected from University of Limpopo, South Africa (23°53”10’S, 29°44”15’E) during summer in September 2018. Light compound microscope and electron microscope were used in the identification of the leaf rust spores. The species identity of the seventeen M. zeyheri trees that form a grove collection at University of Limpopo was confirmed using internal transcribed spacer (ITS) of ribosomal nuclear DNA. DNA extraction and sequencing was done with the help of Inqaba Biotechnologies. Obtained DNA sequences were aligned using CLUSTALX (2.0), with the phylogenetic tree constructed through the neighbour-joining method (NJM) in MEGA v. 5.1 programme. Evolutionary distances were computed using the Juke– Cantor method. Phytochemicals in leaves were identified and quantified using Liquid chromatography–mass spectrometry (LC–MS) at ARC-VOP. The pustules on the collected leaves contained reddish brown spores. The uredospores were oval and ellipsoidal under a light microscope. The size of spores ranged between 35-37 × 24-26 µm. The cell walls showed bilaminate structures with the outer layer hyaline. The warts were rod shaped with one subequatorial germ pore. The most common identified endophytic fungi observed in all M. zeyheri leaves were Teratosphaeria species, Zeloasperium species, Pezizomycotina. In addition, endophytes such as Cladosporium species, Aspergillus species, Phyllosticta species and Epicoccum species were also identified to be associated with some M. zeyheri trees. There were significant differences on the level of tannins, flavonoids, proteins and phenolics among the M. zeyheri trees. The highest level of tannins was 7.2151 mg/g and the lowest being 2.7232 mg/g. The highest level of flavonoids was 1.1537 mg/g the lowest being 0.0123 mg/g. The level of phenolics among the trees ranged from 2.4749 mg/g to 1.5788 mg/g. Protein content ranged from 5.3100% to 2.7967% among the trees. Very high levels of tannins, flavonoids, phenolics among the trees when compared with others studies indicate the potential role of these metabolites in previously reported resistance of M. zeyheri to a number of pests. The morphological characteristics of the identified leaf rust pathogen causing rust symptoms on M. zeyheri in South Africa is more similar to Maravalia species previously isolated from M. caffra. And as such, this finding is paramount, as it is the first report of association between the pathogen and the plant. Teratosphaeria species has been associated with stem cancer in Eucalyptus trees, its presence in M. zeyheri species in asymptomatic plants is a major find since the tree is common in Limpopo and Mpumalanga, Provinces well known for forestry production making M. zeyheri a potential host for pathogens of commercial forestry production. Other endophytes observed such as Aspergillus species, Phyllosticta species and Cladosporium species have been shown to protect plants against some pests and pathogenic organism. Further studies to determine the direct role of identified phytochemicals and endophytes in the resistance of M. zeyheri to pests needs to be conducted
Thesis (M. Sc. Agriculture (Plant Protection)) -- University of Limpopo, 2021
Keywords: Mmupudu zeyheri tree; South Africa; Coffee rust diseases; Leaves -- Diseases and pests; Plant -- Pathogens